Towards a new framework of English language learning in Malaysian preschools - Mohamed Salleh, Rabiah Tul Adawiyah; Lotfie, Maskanah Mohammad; Md. Zamin, Ainul Azmin; Di Biase, Bruno; Kawaguchi, Satomi (Universiti Pendidikan Sultan Idris, 2020)
At the preschool level in Malaysia, all preschools, including those from public and private sectors are required to follow the guidelines stated in the National Preschool Standard-based Curriculum (NPSC) issued by the Ministry of Education (MOE) in 2017. However, the NPSC is very general and schools are not provided with any further guidance on the program, which leads to some preschools, mainly private ones, to supplement their curriculum by subscribing to various private education franchisors available on the market. There seems to be a need to propose improvements to current curriculum practices. It is proposed that this is best done by investigating the theoretical foundations of language learning. In particular, this paper discusses Pienemann’s Processability Theory (1998, 2005) and elaborates on the Developmentally Moderated Focus-on-Form instruction (DMFonF) (Di Biase, 2002,2008). It proposes the development of a new model of English language learning based on the latter leading towards a new framework aiming to assist teachers, linguists and syllabus-designers to create a developmentally moderated English curriculum.